The Timer Compression of Data and Information - Skuratovskii, Ruslan; Osadchyy, Yevgen; Osadchyy, Volodymyr (2020 IEEE Third International Conference on Data Stream Mining & Processing (DSMP), 2020)
The ability to find short representations, i.e. to compress data, is crucial for many intelligent systems. This paper is devoted to data compression and a transform-based quantitative data compression technique involving quick enumeration in a unary-binary time-based numeral system (NS). The symbols comprising the alphabets of human-computer interaction languages (HCIL), which are used in an informational message (IM), are collected in primary code tables, such as the ASCII table. The statistical-oriented data compression method using unconventional timer encryption and encoding information are proposed by us. It was constructed probability - discrete model of the set of character sequences and characterized some probabilistic algorithms associated with the recovery of text by its public key and its cipher. We find the possibility of parallel implementation of this method by building a block of timer tags. The necessary estimations of complexity are obtained. The method can be used to compress SMS messages. Probabilistic-statistical analysis and evaluation of their effectiveness are obtained.